Increase Ability Know English Vocabulary Through the Interactive Whiteboard for Group B Children at Nurul Hidayah Kindergarten, Purwakarta 2025 - Sulastri, Dina; Mulyanti, Fitrah; Priyanti, Nina Yuminar (Peneliti.net, 2025)
This study aims to determine the effect of using interactive whiteboard media on improving early childhood skills in recognizing basic English vocabulary at Nurul Hidayah Kindergarten, Kiarapedes, Purwakarta, and analyze changes in children's learning behavior after the media's implementation. The method used is classroom action research (CAR) with three cycles: pre-cycle, cycle I, and cycle II. The results showed that the level of active participation of children increased significantly, from 30 in the pre-cycle to 71 in the first cycle, reaching 75 in the second cycle, and reaching 85 in the post-cycle. The use of interactive whiteboards encouraged children's engagement in the learning process, improving verbal responses, vocabulary comprehension, and enthusiasm for learning activities. Children were able to recognize and use English vocabulary independently and spontaneously. Changes in learning behavior are also evident in increased self-confidence, learning initiative, and collaboration among children during learning. Interactive media has proven effective as a visual and kinesthetic aid that supports the cognitive and affective development of early childhood. From these findings, it can be concluded that interactive whiteboard media has a positive contribution to English learning at the kindergarten level and is worthy of being developed more widely as part of early childhood education innovation.